2022
DOI: 10.1177/15266028221090441
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes of the Endurant and Excluder Stent Grafts for Endovascular Aneurysm Repair in a Japanese Cohort

Abstract: Purpose: To compare the long-term outcomes of the most widely used third-generation stent grafts, the Endurant and Excluder stent grafts, in Japanese patients using a multicenter registry. Materials and Methods: A retrospective analysis of endovascular aneurysm repairs for abdominal aortic and iliac artery aneurysms using either the Endurant or the Excluder stent grafts from January 2012 to July 2019 at 10 Japanese hospitals was performed. Results: A total of 332 and 378 repairs using the Endurant and Excluder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Gore & Associates, Inc, Flagstaff, Arizona, USA) and 40.7% (Endurant). 20,21 Sac expansion was one of the adverse outcomes after EVAR that might require future reinterventions. The nationwide EVAR registry data in Japan revealed that 23.3% of EVAR patients demonstrated a sac expansion of >5 mm at five years.…”
Section: Discussionmentioning
confidence: 99%
“…Gore & Associates, Inc, Flagstaff, Arizona, USA) and 40.7% (Endurant). 20,21 Sac expansion was one of the adverse outcomes after EVAR that might require future reinterventions. The nationwide EVAR registry data in Japan revealed that 23.3% of EVAR patients demonstrated a sac expansion of >5 mm at five years.…”
Section: Discussionmentioning
confidence: 99%